Phantom validation of Monte Carlo modeling for noncontact depth sensitive fluorescence measurements in an epithelial tissue model - Ong, Yi Hong (2015)
Experimental investigation and optimization of various optical parameters in the design of depth sensitive optical measurements in layered tissues would require a huge amount of time and resources. A computational method to model light transport in layered tissues using Monte Carlo simulations has been developed for decades to reduce the cost incurred during this process. In this work, we employed the Monte Carlo method to investigate the depth sensitivity achieved by various illumination and detection configurations including both the traditional cone configurations and new cone shell configurations, which are implemented by convex or axicon lenses. Phantom experiments have been carried out to validate the Monte Carlo modeling of fluorescence in a two-layered turbid, epithelial tissue model. The measured fluorescence and depth sensitivity of different illumination–detection configurations were compared with each other. The results indicate excellent agreement between the experimental and simulation results in the trends of fluorescence intensity and depth sensitivity. The findings of this study and the development of the Monte Carlo method for noncontact setups provide useful insight and assistance in the planning and optimization of optical designs for depth sensitive fluorescence measurements.